Education as a Soft Power Tool in Russian Foreign Policy - A. V. Torkunov (Vestnik MGIMO-Universiteta)
The article analyses the potential of Russian tertiary education as a tool of long term influence in world politics. It makes a coherent review of a changing nature of leadership in world politics, shows advantages and disadvantages of Russian education as a soft power tool, evaluates the current government initiatives to improve the quality and attractiveness of Russian universities and colleges.